Experience of Publication Epigraphical Memorial Scripts in Lithuania in Nineteenth Century - Tolkačevski, Kšištof (Senoji Lietuvos literatūra, 2015)
Author in this article defines epigraphical memorial scripts, discusses some of aspects of publication epitaphs in the nineteenth century. The historical context of publication epitaphs is drawn by analysis of ideological currents in Europe (such as preromanticism, romanticism, and positivism), situation of science and publishing. Article also includes extended list of publications of epitaphs from nineteenth century. Furthermore, article examines publishing situation in Lithuania, discusses life and social work of some of more or less known publishers (Józef Ignacy Kraszewski, Adam Honory Kirkor, Joachim Lelewel, Eustachy Tyszkiewicz). The paper also examines published epitaphs choice and their contents.
Keywords: -